ZnO gap engineering by doping with III–V compounds. (6th January 2016) - Andriotis, A N; Menon, M
Abstract: Gap engineering of ZnO by codoping it with III–V materials is investigated using model and ab initio calculation. Our results show that the codoped materials (ZnO)1− x (III–V) x, where (III–V) stands for GaN, AlN, AlP, BN, BP exhibit energy band gaps that get smaller as the dopant concentrations x is increased. Even at a very small dopant concentration the obtained band gaps are found to be much smaller than that of ZnO making the studied (ZnO)1− x (III–V) x materials promising candidates for photoelectrochemical water splitting.